Research of the influence of pumping stations on the modes of electric power systems - Obid Y. Nurmatov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: the industries that consume the most electricity are the electrical systems of large pumping stations, oil and water pipelines. Therefore, increasing the energy efficiency of powerful pumping stations and optimizing their modes is one of the urgent tasks. Aim: consider a method for analyzing the impact of pumping stations on the operating modes of electric power systems. Methods: To solve the set tasks, methods for calculating steady-state modes of electric power systems, calculation methods based on the Park-Gorev-Zhukovsky equations, and methods for determining hydraulic shock and theories of stability of electrical systems were used. Results: the steady state and transient modes of complex electric power systems were studied taking into account pumping stations